2006
DOI: 10.1042/bj20060078
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, expression and characterization of pyridoxamine–pyruvate aminotransferase

Abstract: Pyridoxamine-pyruvate aminotransferase is a PLP (pyridoxal 5'-phosphate) (a coenzyme form of vitamin B6)-independent aminotransferase which catalyses a reversible transamination reaction between pyridoxamine and pyruvate to form pyridoxal and L-alanine. The gene encoding the enzyme has been identified, cloned and overexpressed for the first time. The mlr6806 gene on the chromosome of a symbiotic nitrogen-fixing bacterium, Mesorhizobium loti, encoded the enzyme, which consists of 393 amino acid residues. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
23
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Sequence alignment of PPAT with other class V aminotransferases showed that the amino acid residues that have been shown to interact with PLP, based on the crystallography of E. coli phosphoserine aminotransferase (15) and human alanine-glyoxylate aminotransferase (AGAT; Ref. 16), were conserved in PPAT, and it was suggested that PL is held through interaction with these amino acid residues in the active site of PPAT (13). The predicted active site structure of PPAT suggested that PLP cannot bind to the enzyme because the bulky side chain of an amino acid residue located in the phosphate-binding space in PLP-dependent aminotransferases prevents the approach of PLP to the active site of PPAT (13).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Sequence alignment of PPAT with other class V aminotransferases showed that the amino acid residues that have been shown to interact with PLP, based on the crystallography of E. coli phosphoserine aminotransferase (15) and human alanine-glyoxylate aminotransferase (AGAT; Ref. 16), were conserved in PPAT, and it was suggested that PL is held through interaction with these amino acid residues in the active site of PPAT (13). The predicted active site structure of PPAT suggested that PLP cannot bind to the enzyme because the bulky side chain of an amino acid residue located in the phosphate-binding space in PLP-dependent aminotransferases prevents the approach of PLP to the active site of PPAT (13).…”
mentioning
confidence: 99%
“…16), were conserved in PPAT, and it was suggested that PL is held through interaction with these amino acid residues in the active site of PPAT (13). The predicted active site structure of PPAT suggested that PLP cannot bind to the enzyme because the bulky side chain of an amino acid residue located in the phosphate-binding space in PLP-dependent aminotransferases prevents the approach of PLP to the active site of PPAT (13). One of the aims of this study was to determine the amino acid residue preventing the binding of PLP, and the extent to which PPAT can be converted to PMP-pyruvate (PLP-L-alanine) aminotransferase through mutation of a relevant residue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first enzyme for degradation of pyridoxine is pyridoxine 4-oxidase ( 4 , 5 ) and that for pyridoxamine is pyridoxamine-pyruvate aminotransferase ( 6 ). The second, third, seventh enzymes are pyridoxal 4-dehydrogenase ( 7 ), 4-pyridoxolactonase ( 8 ), and MHPC dioxygenase ( 9 ), respectively.…”
mentioning
confidence: 99%
“…1B. The enzyme reaction is the final step in degradation pathway I for vitamin B 6 (pyridoxine, pyridoxamine, and pyridoxal) ( 1 ). The enzyme was purified from the crude extract of Pseudomonas MA-1 cells grown on pyridoxine as a sole carbon source, and some properties were characterized ( 2 , 3 ).…”
mentioning
confidence: 99%